Transport variability-driving mechanisms in Flemish Pass at the western boundary of the Subpolar North Atlantic - Varotsou, Eirini (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2016)
The aim of this study is to analyse the Upper Labrador Sea Water (ULSW) volume transport variability at Flemish Pass and in the Deep Western Boundary Current (DWBC) at 47°N and at 53°N along the topographic slope of the Continental Shelf at the Grand Banks of Newfoundland. In the focus of this study are the physical mechanisms governing the transport variability of ULSW at various timescales using monthly (from 1960-2009) and daily (from 2003-2009) model data from an 8-km resolution numerical ocean model (MITgcm). In order to quantify the southward USLW volume transport, the modeled monthly outputs were used. The average model transport of ULSW decreases southwards from 6.7 Sv at 53°N to 4.5 Sv at 45°N due to interior pathways in the Labrador Sea and in the Newfoundland Basin. The largest fraction of the total ULSW volume transport goes around Flemish Cap within the Deep Western Boundary Current (70%) but a signiﬁcant part goes through Flemish Pass (20%). At seasonal and interannual timescales, the temporal evolution of the ULSW volume transport variability at Flemish Pass presents a distinct behavior when compared to the variability in the DWBC at 47°N and to the upstream ﬂuctuations at 53°N. Other physical parameters are taken into consideration for the examination of the behavior of the transport variability at Flemish Pass. These parameters include the North Atlantic Oscillation (NAO) index, the local Ekman transport, the rate of ULSW formation in the Labrador Sea, the position of the North Atlantic Current (NAC) relative to the slope and the averaged transport in the subpolar gyre. The relationship between these physical processes and the ULSW transports at each section is tested using a running correlation method. Weakened or strengthened transport of ULSW through Flemish Pass coincides with the eﬀect either of the local atmospheric forcing or of changes of the NAC’s position. The transport variability in the DWBC at 47°N is caused by upstream ﬂow ﬂuctuations and changes in the rate of ULSW formation. At ...